Study on Eco-Environmental Effects of Land-Use Transitions and Their Influencing Factors in the Central and Southern Liaoning Urban Agglomeration: A Production–Living–Ecological Perspective - Ruiqiu Pang; Ning Hu; Jingrui Zhou; Dongqi Sun; Hongying Ye (Land, 2022)
From the perspective of the production–living–ecological space, this paper reclassifies the land-use categories in the central and southern Liaoning urban agglomeration in the years 1990, 2000, 2010 and 2018. It then quantitatively analyzes the spatiotemporal evolution characteristics of land-use transitions by adopting the land-use transfer matrix and other methods. This paper further uses the eco-environmental quality index and ecological contribution rate to explore the eco-environmental effects of the land-use transition. Finally, it identifies the influencing factors of the eco-environmental effect and the spatial differentiation law of the effect in the study area through the multi-scale geographically weighted regression (MGWR) model. The main conclusions reached are as follows: (1) During the study period, a slow increase was seen in the ecological land of the central and southern Liaoning urban agglomeration. A sharp decline occurred in the production land, and a rapid rise was found in the living land. (2) From 1990 to 2018, the eco-environmental quality index in the study region showed significant spatial differentiation, with the distribution characteristics being high in the east and low in the west. The areas have expanded and spread along the Shenyang-Dalian axis to form medium-low quality agglomerations. The encroachment of agricultural production land and urban and rural living land on forest ecological land is the main contributor to the deterioration of the eco-environmental quality during the study period. (3) Compared with the geographically weighted regression model and the ordinary least squares model, a remarkable advancement can be seen in the MGWR model, which is more suitable for research on the influencing factors of eco-environmental quality. In addition, different influencing factors have significant spatial differences in the degree and scale of impact.